Determination of 226Ra In Fish Using Liquid Scintillation Analysis - Thompson, Manuela A. (My University, 2012)
226Ra is a radionuclide of much concern since it poses a high risk of radio-toxicity when ingested and is well known for its invariably long half life of 1600 years. As such 226Ra concentrations were measured in whole body tissue of fathead minnows (Pimephales promelas) in an experimental set up. Fathead minnows obtained were about two months old and fed on a Radium-226 spiked diet until 115 days. A simple and direct method to determine 226Ra ingested by fish using a homogeneous liquid scintillation counting was developed. The study consisted of three groups; a sham, Radium treatment and acid treatment. Fathead minnows were sampled 75 and 115 days after feeding, and the following end points; mass (w/w), length, specific growth rate, condition factor and radionuclide measurements obtained. Mean end point results were (0.24 ± 0.03 g), (2.78 ± 0.1 cm), (1.75 ± 0.13 % day-1), (1.10 ± 0.06 g cm-3) and (577.06 ± 572.13 mBq g-1) respectively. Also mean total 226Ra level was calculated as (1911.43 ± 868.64 mBq g-1) while the activity in sham and acid treatment resulted in levels below the Minimum Detectable Activity of 7.46 mBq g-1. The mean rate of 226Ra accumulation, known as the concentration factor, by the fathead minnows was determined as 0.35 ± 0.19. Assuming that the 226Ra Isotope is evenly distributed in the fish whole body, the derived dose rate was found to be 5.26 μGy h-1.
Keywords: Radium-226; Activity Concentration; Dose rate; Fathead Minnow; Other Physics; Other Physics